ELANG SEBAGAI KONSEP PENCIPTAAN KARYA SENI GRAFIS - DICKY FEBRI RAMADHAN, Dr. Budiwirman, M.Pd., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2018)
The eagle is a bird of prey, has special features of large body size, sharppointy beak, and sharp-nailed finger, the characteristics of the eagle to be aninspiration in creating a work of art. The purpose of the creation of this work is tovisualize the eagle as a concept of creating graphic artwork using relief print(hardboard cut) technique. After performing a series of long creation process thencreated 10 pieces of work, namely: 1) Monitoring, 2) Starting, 3) Storming, 4)Eating, 5) Anger, 6) Alone, 7) Eagle Eyes, 8) devotion, 9) Compassion, 10) FinalPoint. Through this work is expected to arouse the spirit in the work of art, andused as a reference and reference in the manufacture of graphic artwork.Keywords: Eagle, Graphic, Hardboard Cut